Semantic Relation Extraction by Conditional Random Fields from Turkish Wikipedia Pages - Girgin, Canan; Diri, Banu (IEEE, 2014)
Relations between entities constitute the most important fundamental parts of semantic search technologies. The products that use semantic search technologies include datastores which keep relations between entities in their infrastructures. Various Relation Extraction applications are done in the extraction of the relations between entities. In this study, Conditional Random Fields has been used to extract extract relations between entities from Turkish Wikipedia pages.
Keywords: relation extraction; natural language processing; conditional random fields; wikipedia; semantic search; Engineering; Telecommunications